Synthesis of novel periodic mesoporous organosilicas with large content of lysine‐bridged organosilane skeleton. (1st December 2017) - Wang, Jianqiang; Gu, Changqing; Zhou, Man; Zhang, Wenqi; Wang, Zhiwei; Lv, Mengyuan; Guo, Cheng; Sun, Linbing
Abstract : Novel periodic mesoporous organosilicas (PMOs) as functional nanomaterials based on the skeleton of lysine were synthesised by the co‐condensation of lysine‐bridged organosilicane (Lys‐BOS) and tetraethyl orthosilicate in acidic medium using P123 as template. Furthermore, a large content of Lys‐BOS was incorporated into the silica framework. Amino acid organosilicane (Lys‐BOS) was first prepared by the multi‐step reaction between traditional orgnaosilicane [(3‐aminopropyl) triethoxysilane] and carboxyl protected lysine. The small‐angle X‐ray diffraction and N2 adsorption–desorption isotherms indicate that these PMO materials still retain ordered mesostructure in the high molar concentration of Lys‐BOS. Fourier‐transform infrared spectroscopy confirms that lysine is incorporated in the framework of the PMO materials.